De feiticeiras diabólicas a auxiliares na empresa missionária: as atuações das mulheres Tupinambá no Maranhão franco-ameríndio (1594-1615) - CONCEIÇÃO, Karen Cristina Costa da (2019)
The purpose of this dissertation is to understand the resistance process of Tupinambá do Maranhão indigenous women between the years 1595 and 1615 in view of the implantation of the Equinocial France enterprise, highlighting the forms of resistance, in view of the imposition of the Western Christian gender. Taking into account the hypothesis that the resistance of these indigenous women is configured as a process of recognition of the value of their roles for the operation of the French colonial enterprise in Maranhão. We believe that these indigenous women, seeing their spaces of power limited by the rules implanted by the colonizers to that society, identified the weaknesses within the social logic in which they were and, consequently, the experience acquired in these spaces enabled the creation of other logics that, in most sometimes differed from those put by the colonizers.